DIGITAL MEDIA DEVELOPMENT FOR PRE-SERVICE ENGLISH TEACHERS IN EFL CLASS: DIGITAL STORYTELLING FOR WRITING SKILL - Arfiyan Ridwan (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
Digital Story Telling (DST) media is one type of learning media that combines aspects of image visualization with sound effects. The merging of these two aspects takes advantage of the Audacity program and operates it with Windows Movie Maker. Visualization of images can be made freely by the designer and creator of the media. For educational purposes, images can be in the form of natural phenomena related to the concept of science about the material to be taught to students. The method used in this study uses a quasi-experimental method (quasi). This research was carried out to find out how much influence the use of digital storytelling-based media had on students' writing skills when viewed from their learning style. In this study, the population taken was students in semester 6 and 8 of the English Education Study Program at STKIP PGRI Bangkalan a number of 56 students. Before using the instrument to collect data, the instrument used needs to be tested first to determine the level of Validity Test, Test Reality Test, Normality data, Homogeneity Test (Similarity of Variance), after that a hypothesis test is carried out to answer the problem formulation using the Analysis of Covariance Test (ANCOVA) measurement. It can be seen that the P value is lower than alpha (0.05) meaning that the use of DST is effective for students’ writing skill in recount text.